Prevalence and factors associated with modern contraceptive discontinuation among reproductive age group women, a community based cross-sectional study in Humera town, northern Ethiopia - Nigisti Belete; Ayalnesh Zemene; Hadgay Hagos; Abere Yekoye (BMC, 2018)
Abstract Background Contraceptive prevalence rate (CPR) for married women aged 15-49 in Ethiopia is 36%, with 35% using modern methods and 1% using traditional methods. However, the discontinuation rate is fairly high. Women usually discontinue contraception use for fertility and method related reasons without adopting an alternate method which in turn leads to many health risks such as unwanted pregnancy, unplanned childbearing, miscarriage, abortion, leads to morbidity and mortality among mothers and newborns. The purpose of this study was to determine the prevalence of modern contraceptive discontinuation and to identify predicting factors. Methods A community- based cross- sectional study was conducted in Humera town among 321 married women of reproductive age (15-49 yrs.) who had a history of modern contraceptive use. Systematic sampling technique was employed to select study participants and data was collected by BSc health extension workers using interviewer -administered questionnaire. EPI-INFO (V-7) and SPSS (V-23) software were used for entry and analysis respectively. Descriptive statistics and logistic regression analysis were used to present results accordingly. P- Value < 0.05 was used as a cut point for statistical significance. Results The magnitude of modern contraceptive discontinuation was 27.1%. Number of desired children (AOR = 2.83 95% CI = 1.16, 6.89), experience of side effects (AOR = 3 95% CI = 1.2, 7.58), discussion with female friend (AOR = 3.26 95% CI = 1.27, 8.36), counseled on side effects (AOR = 6.55 95% CI = 2.21, 19.39), number of male children (AOR = 2.51 95% CI = 1.06, 5.96), absence of husband support (AOR = 12.99 95% CI = 4.59, 36.78) and presence of community prohibition (AOR = 6.88 95% CI = 3.05, 15.51) were identified as predicting factors for modern contraceptive discontinuation. Conclusion Magnitude of modern contraceptive discontinuation among reproductive age group women in Humera was relatively high. Increasing community awareness, involving partners and pre dispensation counseling might help to reduce discontinuation and its consequences. Various targeted messages are also needed to dispel misconception at community level.